In cases of sexual violence, justice can come from outside the courts (Opinion) - Gobbo, Daniel Del (Toronto Star, 2017)
We need to fundamentally rethink the way that the law handles sexual violence. To do that, we should start by asking survivors what “justice” means to them.
Keywords: Daniel Del Gobbo